Piezoelectric material, piezoelectric element, and electronic device
Patent Information
- Application Number
- JP2021039641
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-03-11
AI Technical Summary
【0024】 本発明によれば、鉛を含まず、動作温度範囲内での圧電定数の温度依存性が小さく、圧電定数が良好な圧電材料を提供することができる。本発明の圧電材料は、鉛を使用していないために環境に対する負荷が小さい。
Smart Images

Figure 0007629761000003 
Figure 0007629761000004 
Figure 0007629761000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric material, in particular a lead-free piezoelectric material, and also to a piezoelectric body, a piezoelectric element, a multilayer piezoelectric element, a liquid ejection head, a liquid ejection device, an ultrasonic motor, an optical device, a vibration device, a dust removal device, an imaging device, a piezoelectric acoustic component, an electronic device, an ultrasonic probe, and an ultrasonic diagnostic system, which use the piezoelectric material. [Background technology]
[0002] Lead-containing lead zirconate titanate is a typical piezoelectric material and is used in a variety of piezoelectric devices such as actuators, oscillators, sensors, and filters. However, lead components in discarded piezoelectric materials can leach into soil and cause harm to ecosystems. Therefore, research and development of lead-free piezoelectric materials is being actively conducted to eliminate lead in piezoelectric devices.
[0003] When piezoelectric elements are used in products such as home appliances, or for medical diagnostic purposes, it is required that the piezoelectric performance does not vary significantly within the operating temperature range of the product. If parameters related to piezoelectric performance, such as the electromechanical coupling coefficient and piezoelectric constant, vary significantly with temperature (for example, by 30% or more), it becomes difficult to obtain stable element performance within the operating temperature range. When a piezoelectric material undergoes a phase transition, the piezoelectricity is maximized at the phase transition temperature. Therefore, phase transition is the biggest factor that causes fluctuations in piezoelectric properties. Therefore, if you want to minimize changes in piezoelectric performance within the operating temperature range of a product, you need a piezoelectric material that does not have a phase transition temperature within the operating temperature range.
[0004] Patent Document 1 discloses a piezoelectric material having a main component containing a perovskite-type metal oxide represented by the following general formula (1), a first minor component made of Mn, a second minor component made of Li, and a third minor component made of Bi, characterized in that the Mn content is 0.04 parts by mass or more and 0.36 parts by mass or less, calculated as a metal, per 100 parts by mass of the metal oxide, the Li content α is 0.0012 parts by mass or less (including 0 parts by mass) calculated as a metal, per 100 parts by mass of the metal oxide, and the Bi content β is 0.042 parts by mass or more and 0.850 parts by mass or less, calculated as a metal, per 100 parts by mass of the metal oxide. (Ba 1-x Ca x ) a (Ti 1-y-z Zr y Sn z )O3(1) (In the formula, 0.09≦x≦0.30, 0.025≦y≦0.085, 0≦z≦0.02, 0.986≦a≦1.02)
[0005] The invention described in Patent Document 1 provides a piezoelectric material with little variation in piezoelectric characteristics within the operating temperature range, a high mechanical quality factor, and good piezoelectric characteristics, but the piezoelectric constant is not large and cannot be said to be sufficient. In particular, the phase transition point T to Since the temperature difference between the temperature Tc and the Curie temperature Tc, which is the phase transition point between tetragonal and cubic crystals, is about 140°C, the minimum point of the piezoelectric constant is in the high temperature range (around 50°C) within the operating temperature range. This has led to an issue in which devices that are regularly used at temperatures around 50°C in particular cannot demonstrate sufficient performance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-034121 A Summary of the Invention [Problem to be solved by the invention]
[0007] Conventional techniques have had problems in that the piezoelectric performance of lead-free piezoelectric ceramics varies significantly within the operating temperature range of the piezoelectric element, and the piezoelectric constant is small.
[0008] The present invention has been made to solve such problems, and provides a piezoelectric material that is lead-free, has a small temperature dependency of the piezoelectric constant within the operating temperature range, and has a good piezoelectric constant. The present invention also provides a piezoelectric body, a piezoelectric element, a laminated piezoelectric element, a liquid ejection head, a liquid ejection device, an ultrasonic motor, an optical device, a vibration device, a dust removal device, an imaging device, a piezoelectric acoustic part, an electronic device, an ultrasonic probe, and an ultrasonic diagnostic system that use the piezoelectric material. [Means for solving the problem]
[0009] The piezoelectric material of the present invention for solving the above problems is a piezoelectric material containing an oxide having a perovskite structure containing Ba, Ca, Ti, and Zr, Mn, Bi, and W, x, which is a molar ratio of the Ca to the sum of the Ba and the Ca, 0.085≦x≦ 0.140 and y, which is a molar ratio of Zr to the sum of Ti and Zr, 0.025≦y≦0.085, The sum of the Ba and the Ca relative to the sum of the Ti and the Zr is 0.992 That's all, 0.9994 is as follows: In terms of metal, per 100 parts by mass of the oxide, The Mn content is 0.100 Parts by mass or more 0.240 parts by weight or less, The content of Bi is 0.050 parts by mass or more and 0.240 parts by mass or less, The content of W is 0.104 Parts by weight or more and 0.380 parts by weight or less can be, The average equivalent circular diameter of the crystals of the piezoelectric material is 5.3 μm or more and 9.7 μm or less. It is characterized in that:
[0010] The piezoelectric material of the present invention is characterized in that it is polarized. 。
[0011] The oxide of the present invention is represented by the following general formula (1): (Ba 1-x Ca x ) a (Ti 1-y Zr y )O3(1) (0.085≦x≦0. 140 , 0.025≦y≦0.085, 0. 992 ≦a≦ 0.9994 ) is a piezoelectric material.
[0012] The piezoelectric material of the present invention is characterized in that it has a dielectric loss tangent of 0.010 or less at a frequency of 1 kHz.
[0013] The piezoelectric body of the present invention is characterized in that it contains the above-mentioned piezoelectric material. The piezoelectric element of the present invention is a piezoelectric element having at least an electrode and a piezoelectric material portion, and is characterized in that the piezoelectric material portion contains the piezoelectric material.
[0014] The laminated piezoelectric element of the present invention is a piezoelectric element in which electrodes and piezoelectric material portions are alternately laminated, characterized in that the electrodes contain Ag and Pd, and the mass ratio M1 / M2 of the Ag content M1 to the Pd content M2 satisfies 0.25≦M1 / M2≦4.0.
[0015] The piezoelectric element is characterized in that the electrodes contain at least one of Ni and Cu.
[0016] The liquid ejection head of the present invention is characterized by having at least a liquid chamber having a vibration section in which the piezoelectric element or the laminated piezoelectric element is disposed, and an ejection port communicating with the liquid chamber.
[0017] The liquid ejection apparatus of the present invention is characterized by comprising a mounting unit for a transfer object and the liquid ejection head.
[0018] The vibration type actuator of the present invention is characterized by comprising a vibrating body on which the piezoelectric element or the laminated piezoelectric element is disposed, and a contact body which comes into contact with the vibrating body.
[0019] The optical device of the present invention is characterized in that a drive section includes the vibration actuator. The vibration device of the present invention is characterized by having a vibrating body in which the piezoelectric element or the laminated piezoelectric element is disposed on a vibration plate.
[0020] The dust removing device of the present invention is characterized in that a vibration section includes the vibration device. An imaging apparatus according to the present invention includes at least the dust removal device and an imaging element unit, and is characterized in that a diaphragm of the dust removal device is provided on the light receiving surface side of the imaging element unit.
[0021] The ultrasonic probe of the present invention is characterized by comprising a transducer having the piezoelectric element.
[0022] The ultrasonic diagnostic system of the present invention is characterized by comprising the ultrasonic probe and a receiving unit that receives a signal output from the ultrasonic probe.
[0023] An electronic device according to the present invention is characterized in that it is provided with a piezoelectric acoustic component including the piezoelectric element or the laminated piezoelectric element. Effect of the Invention
[0024] According to the present invention, it is possible to provide a piezoelectric material that is lead-free, has a small temperature dependency of the piezoelectric constant within the operating temperature range, and has a good piezoelectric constant. Since the piezoelectric material of the present invention does not use lead, it has a small load on the environment. [Brief description of the drawings]
[0025] [Figure 1] 1 is a schematic diagram showing an embodiment of a configuration of a piezoelectric element of the present invention. [Diagram 2]1 is a schematic cross-sectional view showing an embodiment of a configuration of a multilayer piezoelectric element of the present invention. [Diagram 3] 1 is a schematic diagram showing an embodiment of the configuration of a liquid ejection head of the present invention. [Figure 4] 1 is a schematic diagram showing an embodiment of a liquid ejection device of the present invention. [Diagram 5] 1 is a schematic diagram showing an embodiment of a liquid ejection device of the present invention. [Figure 6] 1 is a schematic diagram showing an embodiment of the configuration of an ultrasonic motor of the present invention. [Figure 7] 1 is a schematic diagram showing an embodiment of an optical instrument of the present invention. [Figure 8] 1 is a schematic diagram showing an embodiment of an optical instrument of the present invention. [Figure 9] 1 is a schematic diagram showing an embodiment in which a vibration device of the present invention is used as a dust removing device. [Figure 10] 3 is a schematic diagram illustrating a configuration of a piezoelectric element in the dust removing device of the present invention. [Figure 11] 2A to 2C are schematic diagrams illustrating the vibration principle of the dust removing device of the present invention. [Figure 12] 1 is a schematic diagram showing an embodiment of an imaging device of the present invention. [Figure 13] 1 is a schematic diagram showing an embodiment of an imaging device of the present invention. [Figure 14] 1 is a schematic diagram showing an embodiment of an electronic device of the present invention. [Figure 15] 1 is a schematic diagram illustrating an embodiment of an ultrasonic probe of the present invention. [Figure 16] FIG. 1 is a schematic diagram illustrating an embodiment of an ultrasound diagnostic system of the present invention. [Figure 17] 4 shows the dependence of the piezoelectric constant d33 of the piezoelectric material of the present invention on the amount of W added. [Figure 18] 4 shows the change in piezoelectric constant d33 of the piezoelectric body of the present invention with respect to the environmental temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, an embodiment of the present invention will be described. The present invention provides a lead-free piezoelectric material that is mainly composed of (Ba,Ca)(Ti,Zr)O3, has a small temperature dependence of the piezoelectric constant in the operating temperature range, for example, from 0° C. to 60° C., and has good piezoelectric properties. The piezoelectric material of the present invention can be used in various applications such as memories and sensors by utilizing its ferroelectric properties.
[0027] The piezoelectric material of the present invention is a piezoelectric material containing an oxide having a perovskite structure containing Ba, Ca, Ti, and Zr, Mn, Bi, and W, wherein x, which is a molar ratio of Ca to the sum of the Ba and the Ca, is 0.085≦x≦0.150, y, which is a molar ratio of Zr to the sum of the Ti and the Zr, is 0.025≦y≦0.085, the sum of the Ba and the Ca to the sum of the Ti and the Zr is 0.986 or more and 1.02 or less, and the Mn content is 0.040 parts by mass or more and 0.360 parts by mass or less, the Bi content is 0.050 parts by mass or more and 0.240 parts by mass or less, and the W content is 0.100 parts by mass or more and 0.380 parts by mass or less, calculated as metal, per 100 parts by mass of the oxide.
[0028] The piezoelectric material of the present invention has the following general formula (1): (Ba 1-x Ca x )a(Ti 1-y Zr y )O3(1) It can also be expressed as (0.085≦x≦0.150, 0.025≦y≦0.085, 0.986≦a≦1.02).
[0029] In the present invention, the perovskite metal oxide refers to a metal oxide having a perovskite structure (also called a perovskite structure) as described in the Iwanami Physics and Chemistry Dictionary, 5th Edition (Iwanami Shoten, published February 20, 1998). Metal oxides having a perovskite structure are generally expressed by the chemical formula ABO3. In perovskite metal oxides, elements A and B occupy specific positions of a unit lattice called the A site and B site, respectively, in the form of ions. For example, in a cubic unit lattice, element A is located at the vertices of the cube, and element B is located at the body center. Element O occupies the face center position of the cube as an oxygen anion.
[0030] Here, the content of the subcomponents such as Mn, Bi, W, etc. in "metal conversion" refers to the following: For example, in the case of W, the content of each metal, Ba, Ca, Ti, Zr, Mn, Bi, and W, measured in the piezoelectric material by X-ray fluorescence analysis (XRF), ICP atomic emission spectrometry, atomic absorption spectrometry, etc., is converted into the oxide content of the elements constituting the metal oxide represented by the general formula (1) above, and the total mass is taken as 100, and the content is expressed as the ratio of the mass of W to that of the oxide content.
[0031] The piezoelectric material of the present invention has a perovskite metal oxide as the main phase from the viewpoint of insulation. Whether or not the perovskite metal oxide is the main phase can be determined, for example, by whether or not the maximum diffraction intensity derived from the perovskite metal oxide is 100 times or more the maximum diffraction intensity derived from the impurity phase in X-ray diffraction. If the piezoelectric material is composed only of a perovskite metal oxide, the insulation is the highest, and therefore it is preferable. The "main phase" is when, when the powder X-ray diffraction of the piezoelectric material is performed, the peak with the strongest diffraction intensity is due to the perovskite structure. More preferably, the piezoelectric material is a "single phase" in which almost all of the crystals have a perovskite structure.
[0032] The metal oxide represented by the general formula (1) means that the metal elements located at the A site are Ba and Ca, and the metal elements located at the B site are Ti and Zr. However, some of Ba and Ca may be located at the B site. Similarly, some of Ti and Zr may be located at the A site.
[0033] In the general formula (1), the molar ratio of the B site element to the O element is 1:3. However, even if the element amount ratio is slightly different (for example, 1.00:2.94 to 1.00:3.06), it is still within the scope of the present invention as long as the metal oxide has a perovskite structure as the main phase.
[0034] The form of the piezoelectric material according to the present invention is not limited, and may be any form such as ceramics, powder, single crystal, film, slurry, etc., but ceramics is preferable. In this specification, "ceramics" refers to an aggregate (also called a bulk body) of crystal particles whose basic component is a metal oxide and which is sintered by heat treatment, that is, a so-called polycrystal. It also includes those processed after sintering.
[0035] An oxide having a perovskite structure in which the Ca content x is in the range of 0.085≦x≦0.150 and the Zr content y is in the range of 0.025≦y≦0.085, and the Mn content is 0.04 parts by weight or more and 0.36 parts by weight or less, the Bi content is 0.050 parts by weight or more and 0.240 parts by weight or less, and the W content is 0.100 parts by weight or more and 0.380 parts by weight or less, per 100 parts by weight of the oxide, makes it possible to obtain a good piezoelectric constant within the operating temperature range.
[0036] The range of the Ca content x is 0.085≦x≦0.150. When the Ca content x is less than 0.085, the phase transition temperature from tetragonal to orthorhombic (hereinafter referred to as T to ) becomes higher than −20° C., and as a result, the temperature dependence of the piezoelectric constant becomes large within the operating temperature range.
[0037] On the other hand, when x is greater than 0.150, Ca does not form a solid solution at firing temperatures of 1400°C or less, and an impurity phase, CaTiO3, is generated, decreasing the piezoelectric constant.
[0038] The Zr content y is 0.025≦y≦0.085. If the Zr content y is less than 0.025, the piezoelectricity decreases. If y is greater than 0.085, the phase transition temperature T toThe phase transition temperature T to Piezoelectric materials with a temperature of 0° C. or higher have a large temperature dependency of the piezoelectric constant within the operating temperature range.
[0039] When the Zr content is 0.050 or more, the electromechanical coupling coefficient k 33 Therefore, the Zr content y is preferably in the range of 0.050≦y≦0.085.
[0040] The range of a, which is the ratio of the sum of the moles of Zr and Ti to the sum of the moles of Ba and Ca {a=(Ba+Ca) / (Zr+Ti)}, is 0.986≦a≦1.02. If a is less than 0.986, abnormal grain growth occurs during sintering. Furthermore, the average grain size becomes larger than 20 μm, and the mechanical strength of the material decreases. If a is greater than 1.02, a high-density piezoelectric material cannot be obtained. If the density of the piezoelectric material is low, the piezoelectricity decreases. In the present invention, the density of a sample that is insufficiently sintered is 5% or more lower than that of a high-density sample that is sufficiently sintered. In order to obtain a piezoelectric material with high density and high mechanical strength, the range of a is 0.986≦a≦1.02.
[0041] The piezoelectric material of the present invention contains 0.04 parts by mass or more and 0.36 parts by mass or less of Mn, calculated as a metal, as a first minor component relative to 100 parts by mass of the perovskite metal oxide. When Mn is contained in the above range, the coercive field Ec increases. However, when the Mn content is less than 0.04 parts by mass, the effect of increasing the coercive field Ec cannot be obtained. On the other hand, when the Mn content is more than 0.36 parts by mass, the insulation resistance of the piezoelectric material decreases. When the insulation resistance is low, the dielectric loss tangent at room temperature measured by applying an AC electric field with a frequency of 1 kHz and an electric field strength of 10 V / cm using an impedance analyzer exceeds 0.010.
[0042] The dielectric loss tangent of the piezoelectric material of the present invention at a frequency of 1 kHz is preferably 0.010 or less. When the dielectric loss tangent is 0.010 or less, the piezoelectric material generates little heat and can achieve stable operation even when an electric field of up to 500 V / cm is applied to the piezoelectric material under the driving conditions of the element.
[0043] Mn is not limited to metal Mn, and may be contained in the piezoelectric material as a Mn component, and the form of inclusion is not important. For example, it may be solid-solved in the B site, or may be contained in the grain boundary. Alternatively, the Mn component may be contained in the piezoelectric material in the form of metal, ion, oxide, metal salt, complex, or the like. More preferably, Mn is present from the viewpoint of insulation and sintering ease. The valence of Mn can generally be 4+, 2+, or 3+. This is because, when conductive electrons exist in the crystal (for example, when oxygen defects exist in the crystal, or when a donor element occupies the A site, etc.), the valence of Mn is lowered from 4+ to 3+ or 2+, etc., thereby trapping conductive electrons and improving insulation resistance.
[0044] On the other hand, when the valence of Mn is lower than 4+, such as 2+, Mn becomes an acceptor. When Mn exists as an acceptor in a perovskite structure crystal, holes are generated in the crystal or oxygen vacancies are formed in the crystal.
[0045] If the valence of the added Mn is 2+ or 3+, the holes cannot be compensated for by the introduction of oxygen vacancies alone, and the insulation resistance decreases. Therefore, it is preferable that the majority of Mn is 4+. However, a very small amount of Mn may have a valence lower than 4+ and occupy the B site of the perovskite structure as an acceptor, forming oxygen vacancies. This is because Mn with a valence of 2+ or 3+ and oxygen vacancies form defect dipoles, which can improve the mechanical quality factor of the piezoelectric material. If trivalent Bi occupies the A site, Mn will tend to have a valence lower than 4+ in order to achieve charge balance.
[0046] The valence of a small amount of Mn added to a non-magnetic (diamagnetic) material can be evaluated by measuring the temperature dependence of magnetic susceptibility. Magnetic susceptibility can be measured using a superconducting quantum interference device (SQUID), a vibrating sample magnetometer (VSM), or a magnetic balance. The magnetic susceptibility χ obtained by the measurement generally follows the Curie-Weiss law, expressed by equation (2). Equation (2) χ = C / (T-θ) (C: Curie constant, θ: paramagnetic Curie temperature)
[0047] Generally, when a small amount of Mn is added to a non-magnetic material, the spin S=5 / 2 is when the valence is 2+, S=2 is when the valence is 3+, and S=3 / 2 is when the valence is 4+. Therefore, the Curie constant C converted per unit amount of Mn corresponds to the spin S value at each Mn valence. Therefore, the average valence of Mn in a sample can be evaluated by deriving the Curie constant C from the temperature dependence of the magnetic susceptibility χ.
[0048] In order to evaluate the Curie constant C, it is desirable to measure the temperature dependence of magnetic susceptibility from as low a temperature as possible. This is because the amount of Mn is so small that the magnetic susceptibility value becomes very small at relatively high temperatures such as around room temperature, making measurement difficult. The Curie constant C can be derived from the slope of the straight line obtained by plotting the reciprocal of magnetic susceptibility 1 / χ against temperature T and linearly approximating it.
[0049] The piezoelectric material of the present invention contains 0.050 to 0.240 parts by mass of Bi as an auxiliary component, calculated as a metal, relative to 100 parts by mass of the perovskite metal oxide represented by the general formula (1). The content of Bi in the piezoelectric material can be measured, for example, by ICP-MS composition analysis, and is considered to be 0 parts by mass when it is below the measurement limit of 0.00001 parts by mass. If the content of Bi is less than 0.050 parts by mass, the effect of lowering the phase transition temperature and improving the mechanical quality factor cannot be obtained. If the content of Bi is more than 0.050 parts by mass, the electromechanical coupling coefficient decreases by more than 30% compared to when Bi is not contained.
[0050] In the piezoelectric material of the present invention, Bi may be present at the grain boundaries, or may be dissolved in the perovskite structure of (Ba,Ca)(Ti,Zr)O3.
[0051] When Bi is present at the grain boundaries, the friction between the grains is reduced and the mechanical quality factor is increased. When Bi is dissolved in the perovskite structure of (Ba,Ca)(Ti,Zr)O3, T ot and T toSince the temperature is lowered, the temperature dependency of the piezoelectric constant within the operating temperature range is reduced, and the mechanical quality factor can be improved.
[0052] The location where Bi is present can be evaluated by, for example, X-ray diffraction, electron beam diffraction, an electron microscope, ICP-MS, or the like.
[0053] When Bi is present in the B site, the lattice constant of the perovskite structure increases because the ionic radius of Bi is larger than that of Ti and Zr.
[0054] When Bi is present in the A site, the optimal a value for firing high-density ceramics is lowered. In the phase diagram of BaO and TiO2, a liquid phase exists at high temperatures on the TiO2-rich side of the composition where BaO and TiO2 are in a 1:1 molar ratio. Therefore, when firing BaTiO3 ceramics, if the TiO2 content is greater than the stoichiometric ratio, abnormal grain growth occurs due to liquid phase sintering. On the other hand, if there is a lot of BaO content, sintering does not proceed smoothly and the density of the ceramics decreases. If Bi is present in the A site, the A site content becomes excessive, and the sintering of the ceramics may actually be more difficult. As a result, the density of the ceramics decreases. In such cases, sintering can be promoted by taking measures to lower the a value, and a high-density sample can be obtained.
[0055] The piezoelectric material of the present invention contains, as a subcomponent, 0.100 parts by mass or more and 0.380 parts by mass or less of W, calculated as a metal, per 100 parts by mass of the perovskite metal oxide. The W content in the piezoelectric material can be measured, for example, by ICP-MS composition analysis, and when it is below the measurement limit of 0.00001 parts by mass, it is regarded as 0 parts by mass.
[0056] When the W content is less than 0.100 parts by mass, the piezoelectric constant d 33 When the W content is more than 0.380 parts by mass, the electromechanical coupling coefficient k 33 , piezoelectric constant d 33 becomes smaller.
[0057] W is not limited to metallic W, and it is sufficient that it is contained in the piezoelectric material as a W component, and the form of inclusion does not matter. Normally, it is dissolved in the B site, but it may be contained in the grain boundary. Alternatively, the W component may be contained in the piezoelectric material in the form of metal, ion, oxide, metal salt, complex, etc. The valence of W can generally be 6+, and it enters the B site and acts as a donor.
[0058] Since the ionic radius of W in the B site is smaller than that of Ti and Zr, the c / a ratio of the tetragonal crystal is smaller, and the Curie temperature Tc of the piezoelectric material, which is a perovskite-type metal oxide, is lowered. In addition, since the effect at the phase transition point between tetragonal and orthorhombic crystals is small, W ions in the B site as 6+ have the effect of reducing the tetragonality, facilitating the polarization reversal of the piezoelectricity and increasing the piezoelectric constant.
[0059] For the purpose of facilitating the production of the piezoelectric material of the present invention or adjusting the physical properties of the piezoelectric material of the present invention, up to 1 mol % of Ba and Ca may be replaced with a divalent metal element, such as Sr, and up to 1 mol % of Ti and Zr may be replaced with a tetravalent metal element, such as Hf.
[0060] The density of the sintered body can be measured by, for example, the Archimedes method. In the present invention, the theoretical density (ρ calc. ) versus measured density (ρ meas. ), i.e., the relative density (ρ calc. / ρ meas. ) of 95% or more can be said to be sufficiently high for use as a piezoelectric material.
[0061] Curie temperature T C is the temperature above which the piezoelectricity of a piezoelectric material disappears. In this specification, the temperature at which the dielectric constant becomes maximum near the phase transition temperature between the ferroelectric phase (tetragonal phase) and the paraelectric phase (cubic phase) is defined as T C The dielectric constant is measured, for example, by using an impedance analyzer to apply an AC electric field with a frequency of 1 kHz and a field strength of 10 V / cm.
[0062] The piezoelectric material of the present invention undergoes successive phase transitions from rhombohedral to orthorhombic to tetragonal to cubic as the temperature rises from a low temperature. The phase transition referred to in this specification refers exclusively to the phase transition from tetragonal to orthorhombic. The phase transition temperature can be evaluated using a measurement method similar to the Curie temperature, and the temperature at which the value obtained by differentiating the dielectric constant with respect to the sample temperature is maximized is defined as the phase transition temperature. The crystal system can be evaluated by X-ray diffraction, electron beam diffraction, Raman scattering, or the like.
[0063] One of the factors that reduces the mechanical quality factor is the vibration of the domain walls. In general, the more complex the domain structure, the higher the density of the domain walls and the lower the mechanical quality factor. The crystal orientation of the spontaneous polarization of the orthorhombic or tetragonal perovskite structure is expressed in pseudocubic notation as follows: <110> or <100> In other words, the spatial degree of freedom of spontaneous polarization is lower in the tetragonal structure than in the orthorhombic structure. Therefore, the domain structure is simpler in the tetragonal structure, and the mechanical quality factor is higher even with the same composition. Therefore, it is preferable that the piezoelectric material of the present invention has a tetragonal structure rather than an orthorhombic structure in the operating temperature range.
[0064] Near the phase transition temperature, the dielectric constant and electromechanical coupling coefficient reach their maximums, and Young's modulus reaches its minimum. The piezoelectric constant is a function of these three parameters, and shows a maximum value or an inflection point near the phase transition temperature. Therefore, if a phase transition exists within the operating temperature range of a device, the device's performance will vary drastically with temperature, and the resonant frequency will vary with temperature, making it difficult to control the device. Therefore, it is desirable that the phase transition, which is the greatest factor in the variation of piezoelectric performance, does not exist within the operating temperature range. The farther the phase transition temperature is from the operating temperature range, the lower the temperature dependence of the piezoelectric performance within the operating temperature range, which is preferable.
[0065] In the present invention, by adding W in particular, it is possible to lower only the Curie temperature while maintaining the orthorhombic and tetragonal phase transition temperature. This allows the piezoelectric constant d 33 Between the maximum values of the piezoelectric constant d 33The minimization of the piezoelectric constant d at the high temperature side of the operating temperature range (around 50°C) was remarkable as the Curie temperature approached the high temperature side (around 50°C). 33 This suppresses the decrease in the temperature dependence and improves the temperature stability.
[0066] At this time, the piezoelectric constant d 33 The rate of change is expressed by the following equation (3). Piezoelectric constant d 33 rate of change = (d 33max -d 33min )÷d 33@RT Formula (3)
[0067] Equation (3) expresses the piezoelectric constant d 33 The highest value of (d 33max ) and the lowest value (d 33min ) is the piezoelectric constant d 33 (d 33@RT ) is the piezoelectric constant d 33 The rate of change of the piezoelectric constant d at room temperature is preferably 0.3 or less, and more preferably 0.23 or less. 33 From the viewpoint of device performance, it is preferable that the capacitance is 240 pm / V or more.
[0068] The method for producing the piezoelectric material according to the present invention is not particularly limited. When manufacturing piezoelectric ceramics, a common method can be used in which solid powders of oxides, carbonates, nitrates, oxalates, etc. containing the constituent elements are sintered under normal pressure. The raw materials consist of metal compounds such as Ba compounds, Ca compounds, Ti compounds, Zr compounds, Mn compounds, Bi compounds, and W compounds.
[0069] Usable Ba compounds include barium oxide, barium carbonate, barium oxalate, barium acetate, barium nitrate, barium titanate, barium zirconate, and barium titanate zirconate.
[0070] Examples of Ca compounds that can be used include calcium oxide, calcium carbonate, calcium oxalate, calcium acetate, calcium titanate, and calcium zirconate.
[0071] Usable Ti compounds include titanium oxide, barium titanate, barium titanate zirconate, and calcium titanate.
[0072] Usable Zr compounds include zirconium oxide, barium zirconate, barium zirconate titanate, calcium zirconate, and the like.
[0073] Usable Mn compounds include manganese carbonate, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese acetate, and the like. An example of a usable Bi compound is bismuth oxide. Examples of W compounds that can be used include tungsten oxide and tungsten chloride.
[0074] In addition, the raw material for adjusting the ratio a of the sum of the moles of Ti and Zr to the sum of the moles of Ba and Ca in the piezoelectric ceramic according to the present invention {a=(Ba+Ca) / (Zr+Ti)} is not particularly limited. The same effect can be obtained with any of Ba compounds, Ca compounds, Ti compounds, and Zr compounds.
[0075] The method of granulating the raw powder of the piezoelectric ceramic according to the present invention is not particularly limited. Examples of binders that can be used in granulation include PVA (polyvinyl alcohol), PVB (polyvinyl butyral), and acrylic resins. The amount of binder added is preferably 1 to 10 parts by mass, and more preferably 2 to 5 parts by mass from the viewpoint of increasing the density of the molded body. A mixed powder obtained by mechanically mixing Ba compounds, Ca compounds, Ti compounds, Zr compounds, Mn compounds, Bi compounds, and W compounds may be granulated, or these compounds may be calcined at about 800 to 1300 ° C. and then granulated, or Ba compounds, Ca compounds, Ti compounds, Zr compounds, Mn compounds, and Bi compounds may be calcined and then W compounds may be added simultaneously with the binder. From the viewpoint of making the particle size of the granulated powder more uniform, the most preferable granulation method is the spray drying method.
[0076] There is no particular limitation on the method for producing the piezoelectric ceramic green body according to the present invention. The green body is a solid body produced from raw powder, granulated powder, or slurry. The green body can be produced by uniaxial pressing, cold isostatic pressing, warm isostatic pressing, casting, extrusion, or the like.
[0077] The sintering method of the piezoelectric ceramic according to the present invention is not particularly limited. Examples of the sintering method include sintering in an electric furnace, sintering in a gas furnace, electrical heating, microwave sintering, millimeter wave sintering, HIP (hot isostatic pressing), etc. Sintering in an electric furnace or gas may be performed in a continuous furnace or a batch furnace.
[0078] The sintering temperature of the ceramics in the sintering method is not particularly limited. It is preferable that the temperature is such that each compound reacts and crystals grow sufficiently. The preferred sintering temperature is 1100°C to 1550°C, more preferably 1100°C to 1400°C, from the viewpoint of setting the grain size of the ceramics in the range of 2.0 μm to 12.0 μm. Piezoelectric ceramics sintered in the above temperature range exhibit good piezoelectric performance.
[0079] In order to reproducibly and stably obtain the characteristics of the piezoelectric ceramics obtained by sintering, it is advisable to carry out the sintering process for 2 hours or more and 24 hours or less at a constant sintering temperature within the above range.
[0080] After the piezoelectric ceramic is polished, it is preferable to heat treat it at a temperature of 800°C or higher. Mechanical polishing generates residual stress inside the piezoelectric ceramic, but by heat treating it at 1000°C or higher to the extent that the polished surface does not increase in surface roughness due to grain growth, the residual stress is alleviated and the piezoelectric properties of the piezoelectric ceramic are further improved. It also has the effect of removing raw material powder such as barium carbonate precipitated at the grain boundary. The heat treatment time is not particularly limited, but it is preferable to use an hour or more.
[0081] If the crystal grain size of the piezoelectric material of the present invention exceeds 12.0 μm, the material strength during cutting and polishing may be insufficient, and if the grain size is less than 2.0 μm, the piezoelectricity decreases.
[0082] The term "grain size" in the present invention refers to the "projected area circle equivalent diameter" generally referred to in microscopic observation, and refers to the diameter of a perfect circle having the same area as the projected area of a crystal grain. In the present invention, the method for measuring the grain size is not particularly limited. For example, the grain size can be obtained by photographing the surface of a piezoelectric material with a polarizing microscope or a scanning electron microscope, and then processing the resulting photographic image. Since the optimal magnification differs depending on the grain size of interest, an optical microscope and an electron microscope may be used separately. The circle equivalent diameter may also be obtained from an image of a polished surface or cross section of the material, rather than from the surface of the sintered body.
[0083] When the piezoelectric material of the present invention is used as a film formed on a substrate, the thickness of the piezoelectric material is desirably 200 nm to 10 μm, more desirably 300 nm to 3 μm, because a sufficient electromechanical conversion function as a piezoelectric element can be obtained by setting the film thickness of the piezoelectric material to 200 nm to 10 μm.
[0084] The method of forming the film is not particularly limited. For example, chemical solution deposition (CSD), sol-gel, metal organic chemical vapor deposition (MOCVD), sputtering, pulsed laser deposition (PLD), hydrothermal synthesis, aerosol deposition (AD), etc. are listed. Among these, the most preferred lamination method is chemical solution deposition or sputtering. Chemical solution deposition or sputtering can easily increase the area of the film. The substrate used for the piezoelectric material of the present invention is preferably a single crystal substrate cut and polished on the (001) or (110) plane. By using a single crystal substrate cut and polished on a specific crystal plane, the piezoelectric material film provided on the surface of the substrate can also be strongly oriented in the same direction.
[0085] In the present invention, the piezoelectric body refers to the above-mentioned sintered body, film, etc., which contains a piezoelectric material and has a certain form.
[0086] A piezoelectric element using the piezoelectric material of the present invention will now be described. 1 is a schematic diagram showing one embodiment of the configuration of a piezoelectric element of the present invention. The piezoelectric element of the present invention is a piezoelectric element having at least a first electrode 1, a piezoelectric material part 2, and a second electrode 3, and is characterized in that the piezoelectric material part 2 is the piezoelectric material of the present invention.
[0087] The piezoelectric material according to the present invention can be made into a piezoelectric element having at least a first electrode 1 and a second electrode 3, so that its piezoelectric properties can be evaluated. The first electrode 1 and the second electrode 3 are made of a conductive layer having a thickness of about 5 nm to 10 μm. The material is not particularly limited, and may be any material that is commonly used in piezoelectric elements. For example, metals such as Ti, Pt, Ta, Ir, Sr, In, Sn, Au, Al, Fe, Cr, Ni, Pd, Ag, and Cu, and compounds thereof can be mentioned.
[0088] The first electrode 1 and the second electrode 3 may be made of one of these materials, or may be made by laminating two or more of these materials. The first electrode 1 and the second electrode 3 may be made of different materials.
[0089] The manufacturing method of the first electrode 1 and the second electrode 3 is not limited, and they may be formed by baking a metal paste, or by sputtering, vapor deposition, etc. In addition, both the first electrode 1 and the second electrode 3 may be patterned into a desired shape before use.
[0090] The piezoelectric element has a polarization axis aligned in a certain direction. By aligning the polarization axis in a certain direction, the piezoelectric constant of the piezoelectric element is large.
[0091] The method of polarization of the piezoelectric element is not particularly limited. The polarization process may be performed in air or in silicone oil. The temperature during polarization is preferably 60°C to 150°C, but the optimal conditions vary slightly depending on the composition of the piezoelectric material that constitutes the element. The electric field applied for polarization process is preferably 600V / mm to 2.0kV / mm.
[0092] The piezoelectric constant d of the piezoelectric element 33 , d 31 and the electromechanical quality factor k 33 , k 31 can be calculated based on the measurement results of the resonance frequency and anti-resonance frequency obtained using a commercially available impedance analyzer, in accordance with the Japan Electronics and Information Technology Industries Association standard (JEITA EM-4501). Hereinafter, this method will be referred to as the resonance-anti-resonance method.
[0093] Next, a laminated piezoelectric element using the piezoelectric material of the present invention will be described. (Layered piezoelectric element) The multilayer piezoelectric element according to the present invention is a multilayer piezoelectric element in which a plurality of piezoelectric material layers and a plurality of electrodes including internal electrodes are alternately laminated, and is characterized in that the piezoelectric material layers are made of the piezoelectric material of the present invention.
[0094] 2 is a schematic cross-sectional view showing one embodiment of the configuration of the multilayer piezoelectric element of the present invention. The multilayer piezoelectric element of the present invention is composed of piezoelectric material layers 54 and electrodes including internal electrodes 55, and is a multilayer piezoelectric element in which piezoelectric material layers and layered electrodes are alternately laminated, and is characterized in that the piezoelectric material layers 54 are made of the above-mentioned piezoelectric material. The electrodes may include external electrodes such as a first electrode 51 and a second electrode 53 in addition to the internal electrodes 55.
[0095] Fig. 2(a) shows the configuration of the multilayer piezoelectric element of the present invention in which two piezoelectric material layers 54 and one internal electrode 55 are alternately laminated, and the laminated structure is sandwiched between a first electrode 51 and a second electrode 53, but the number of piezoelectric material layers and internal electrodes may be increased as shown in Fig. 2(b), and there is no limit to the number of layers. The multilayer piezoelectric element in Fig. 2(b) has a configuration in which nine piezoelectric material layers 504 and eight internal electrodes 505 are alternately laminated, and the laminated structure is sandwiched between a first electrode 501 and a second electrode 503, and has external electrodes 506a and 506b for short-circuiting the alternating internal electrodes.
[0096] The size and shape of the internal electrodes 55, 505 and the external electrodes 506a, 506b do not necessarily have to be the same as those of the piezoelectric material layers 54, 504, and they may be divided into a plurality of electrodes.
[0097] The internal electrodes 55, 505 and the external electrodes 506a, 506b, the first electrodes 51, 501 and the second electrodes 53, 503 are made of conductive layers having a thickness of about 5 nm to 10 μm. The material is not particularly limited, and may be any material that is normally used in piezoelectric elements. For example, metals such as Ti, Pt, Ta, Ir, Sr, In, Sn, Au, Al, Fe, Cr, Ni, Pd, Ag, Cu, and compounds thereof may be mentioned. The internal electrodes 55, 505 and the external electrodes 506a, 506b may be made of one of these, or a mixture or alloy of two or more of these, or may be made by laminating two or more of these. Moreover, the multiple electrodes may be made of different materials. From the viewpoint of inexpensive electrode materials, it is preferable that the internal electrodes 55, 505 contain at least one of Ni and Cu. When at least one of Ni and Cu is used for the internal electrodes 55, 505, the multilayer piezoelectric element of the present invention is preferably fired in a reducing atmosphere.
[0098] In the laminated piezoelectric element of the present invention, the internal electrodes preferably contain Ag and Pd, and the mass ratio M1 / M2 of the Ag content M1 to the Pd content M2 is preferably 0.25≦M1 / M2≦4.0. If the mass ratio M1 / M2 is less than 0.25, the sintering temperature of the internal electrodes becomes high, which is undesirable. On the other hand, if the mass ratio M1 / M2 is greater than 4.0, the internal electrodes become island-like and therefore non-uniform within the plane, which is undesirable. More preferably, 0.3≦M1 / M2≦3.0.
[0099] As shown in FIG. 2(b), a plurality of electrodes including the internal electrode 505 may be short-circuited to each other in order to align the phase of the driving voltage. For example, the internal electrode 505a and the first electrode 501 may be short-circuited by the external electrode 506a. The internal electrode 505b and the second electrode 503 may be short-circuited by the external electrode 506b. The internal electrodes 505a and the internal electrodes 505b may be arranged alternately. The form of the short-circuit between the electrodes is not limited. An electrode or wiring for short-circuiting may be provided on the side of the laminated piezoelectric element, or a through-hole penetrating the piezoelectric material layer 504 may be provided and a conductive material may be provided inside the through-hole to short-circuit the electrodes.
[0100] (Liquid ejection head) The liquid ejection head according to the present invention is characterized by having at least a liquid chamber equipped with a vibration part in which the piezoelectric element or the laminated piezoelectric element is arranged, and an ejection port communicating with the liquid chamber. The liquid ejected by the liquid ejection head of the present invention is not particularly limited as long as it is a fluid, and it is possible to eject aqueous liquids such as water, ink, and fuel, as well as non-aqueous liquids.
[0101] Fig. 3 is a schematic diagram showing one embodiment of the configuration of a liquid ejection head of the present invention. As shown in Fig. 3(a) and (b), the liquid ejection head of the present invention is a liquid ejection head having a piezoelectric element 101 of the present invention. The piezoelectric element 101 is a piezoelectric element having at least a first electrode 1011, a piezoelectric material 1012, and a second electrode 1013. The piezoelectric material 1012 is patterned as necessary, as shown in Fig. 3(b).
[0102] 3(b) is a schematic diagram of a liquid ejection head. The liquid ejection head has ejection ports 105, individual liquid chambers 102, communication holes 106 connecting the individual liquid chambers 102 and the ejection ports 105, liquid chamber partitions 104, a common liquid chamber 107, a vibration plate 103, and a piezoelectric element 101. In the figure, the piezoelectric element 101 is rectangular, but the shape may be other than rectangular, such as an ellipse, a circle, or a parallelogram. In general, the piezoelectric material 1012 has a shape that matches the shape of the individual liquid chambers 102.
[0103] The vicinity of the piezoelectric element 101 included in the liquid ejection head of the present invention will be described in detail with reference to Fig. 3(a). Fig. 3(a) is a cross-sectional view in the width direction of the piezoelectric element shown in Fig. 3(b). The cross-sectional shape of the piezoelectric element 101 is shown as a rectangle, but it may also be a trapezoid or an inverted trapezoid.
[0104] In the figure, the first electrode 1011 is used as the lower electrode, and the second electrode 1013 is used as the upper electrode. However, the arrangement of the first electrode 1011 and the second electrode 1013 is not limited to this. For example, the first electrode 1011 may be used as the lower electrode or as the upper electrode. Similarly, the second electrode 1013 may be used as the upper electrode or as the lower electrode. Also, a buffer layer 108 may be present between the diaphragm 103 and the lower electrode. Note that the difference in these names is due to the manufacturing method of the device, and the effects of the present invention can be obtained in either case.
[0105] In the liquid ejection head, the vibration plate 103 moves up and down due to the expansion and contraction of the piezoelectric material 1012, and applies pressure to the liquid in the individual liquid chamber 102. As a result, the liquid is ejected from the ejection port 105. The liquid ejection head of the present invention can be used for printer applications and for manufacturing electronic devices. The thickness of the vibration plate 103 is 1.0 μm or more and 15 μm or less, and preferably 1.5 μm or more and 8 μm or less. The material of the vibration plate is not limited, but is preferably Si. The Si of the vibration plate may be doped with boron or phosphorus. In addition, the buffer layer and the electrode on the vibration plate may be part of the vibration plate. The thickness of the buffer layer 108 is 5 nm or more and 300 nm or less, and preferably 10 nm or more and 200 nm or less. The size of the ejection port 105 is 5 μm or more and 40 μm or less in circle equivalent diameter. The shape of the ejection port 105 may be circular, star-shaped, rectangular, or triangular.
[0106] (Liquid discharge device) Next, the liquid ejection apparatus of the present invention will be described The liquid ejection apparatus of the present invention includes a mounting unit for a transfer object and the liquid ejection head.
[0107] An example of the liquid ejection device of the present invention is an inkjet recording device shown in Fig. 4 and Fig. 5. Fig. 5 shows a state in which exteriors 882 to 885 and 887 of a liquid ejection device (inkjet recording device) 881 shown in Fig. 4 have been removed. The inkjet recording device 881 has an automatic feed unit 897 that automatically feeds recording paper as a transfer medium into a device body 896. The inkjet recording device 881 further has a transport unit 899 that guides the recording paper fed from the automatic feed unit 897 to a predetermined recording position and guides it from the recording position to an outlet 898, a recording unit 891 that performs recording on the recording paper transported to the recording position, and a recovery unit 890 that performs recovery processing on the recording unit 891. The recording unit 891 is provided with a carriage 892 that houses the liquid ejection head of the present invention and is transported back and forth on a rail.
[0108] In such an inkjet recording device, a carriage 892 is moved on rails by an electric signal sent from a computer, and the piezoelectric material is displaced when a drive voltage is applied to electrodes that sandwich the piezoelectric material. This displacement of the piezoelectric material pressurizes the individual liquid chambers 102 via the vibration plate 103 shown in Fig. 3(b), causing ink to be ejected from the ejection ports 105 to perform printing. In the liquid ejection device of the present invention, liquid can be ejected uniformly at high speed.
[0109] While the above example was given as an example of a printer, the liquid ejection device of the present invention can be used as a printing device such as an inkjet recording device such as a facsimile, a multifunction device, or a copier, as well as an industrial liquid ejection device and a drawing device for an object.
[0110] In addition, the user can select a desired object to be transferred depending on the application. The liquid ejection head may be configured to move relatively to the object to be transferred placed on a stage as a placement unit.
[0111] (Ultrasonic motor) The ultrasonic motor according to the present invention is characterized by having at least a vibrating body on which the piezoelectric element or the laminated piezoelectric element is arranged, and a moving body in contact with the vibrating body. FIG. 6 is a schematic diagram showing one embodiment of the configuration of the ultrasonic motor according to the present invention. FIG. 6(a) shows an ultrasonic motor in which the piezoelectric element of the present invention is made of a single plate. The ultrasonic motor has a vibrator 201, a rotor 202 that is in contact with the sliding surface of the vibrator 201 by a pressure force of a pressure spring (not shown), and an output shaft 203 that is integrally provided with the rotor 202. The vibrator 201 is composed of a metal elastic ring 2011, the piezoelectric element 2012 of the present invention, and an organic adhesive 2013 (epoxy-based, cyanoacrylate-based, etc.) that bonds the piezoelectric element 2012 to the elastic ring 2011. The piezoelectric element 2012 of the present invention is composed of a piezoelectric material sandwiched between a first electrode and a second electrode (not shown). When a two-phase alternating voltage with a phase difference of an odd multiple of π / 2 is applied to the piezoelectric element of the present invention, a flexural traveling wave is generated in the vibrator 201, and each point on the sliding surface of the vibrator 201 moves elliptically. When the rotor 202 is pressed against the sliding surface of the vibrator 201, the rotor 202 receives a frictional force from the vibrator 201 and rotates in the opposite direction to the flexural traveling wave. The driven body (not shown) is connected to the output shaft 203 and is driven by the rotational force of the rotor 202. When a voltage is applied to a piezoelectric material, the piezoelectric material expands and contracts due to the piezoelectric transverse effect. When an elastic body such as a metal is connected to the piezoelectric element, the elastic body is bent by the expansion and contraction of the piezoelectric material. The ultrasonic motor of the type described here utilizes this principle. Next, an ultrasonic motor including a piezoelectric element having a laminated structure is illustrated in FIG. 6(b). The vibrator 204 is composed of a laminated piezoelectric element 2042 sandwiched between cylindrical metallic elastic bodies 2041. The laminated piezoelectric element 2042 is an element made of multiple laminated piezoelectric materials (not shown), and has a first electrode and a second electrode on the outer surface of the laminated layer, and an internal electrode on the inner surface of the laminated layer. The metal elastic body 2041 is fastened with bolts to sandwich and fix the laminated piezoelectric element 2042, forming the vibrator 204. By applying alternating voltages with different phases to the laminated piezoelectric element 2042, the vibrator 204 excites two vibrations that are perpendicular to each other. These two vibrations are combined to form a circular vibration that drives the tip of the vibrator 204.A constricted circumferential groove is formed on the top of the vibrator 204 to increase the displacement of the vibration for driving. The rotor 205 is in pressure contact with the vibrator 204 by the pressure spring 206, and obtains frictional force for driving. The rotor 205 is rotatably supported by a bearing.
[0112] (optical equipment) Next, an optical device according to the present invention will be described. The optical device according to the present invention is characterized in that a drive unit thereof includes the ultrasonic motor described above.
[0113] 7(a) and 7(b) are cross-sectional views of the main parts of an interchangeable lens barrel for a single-lens reflex camera, which is an example of a preferred embodiment of the optical device of the present invention. Also, Fig. 8 is an exploded perspective view of an interchangeable lens barrel for a single-lens reflex camera, which is an example of a preferred embodiment of the optical device of the present invention. A fixed barrel 712, a linear guide barrel 713, and a front group barrel 714 are fixed to a detachable mount 711 for the camera. These are fixed members of the interchangeable lens barrel.
[0114] A linear guide groove 713a in the optical axis direction for the focus lens 702 is formed in the linear guide barrel 713. Cam rollers 717a, 717b protruding radially outward are fixed to a rear group barrel 716 holding the focus lens 702 by shaft screws 718, and the cam roller 717a fits into the linear guide groove 713a.
[0115] A cam ring 715 is rotatably fitted on the inner periphery of the linear guide barrel 713. The relative movement between the linear guide barrel 713 and the cam ring 715 in the optical axis direction is restricted by a roller 719 fixed to the cam ring 715 fitting into a circumferential groove 713b of the linear guide barrel 713. A cam groove 715a for the focus lens 702 is formed in this cam ring 715, and the above-mentioned cam roller 717b is fitted into the cam groove 715a at the same time.
[0116] A rotation transmission ring 720 is disposed on the outer periphery of the fixed barrel 712, and is held by a ball race 727 so as to be rotatable at a fixed position relative to the fixed barrel 712. In the rotation transmission ring 720, rollers 722 are rotatably held on shafts 720f extending radially from the rotation transmission ring 720, and large diameter portions 722a of the rollers 722 are in contact with a mount side end face 724b of the manual focus ring 724. In addition, small diameter portions 722b of the rollers 722 are in contact with a joining member 729. Six rollers 722 are disposed at equal intervals on the outer periphery of the rotation transmission ring 720, and each roller is configured as described above.
[0117] A low-friction sheet (washer member) 733 is disposed on the inner diameter portion of the manual focus ring 724, and this low-friction sheet is sandwiched between a mount side end face 712a of the fixed barrel 712 and a front end face 724a of the manual focus ring 724. The outer diameter surface of the low-friction sheet 733 is ring-shaped and radially fits into an inner diameter 724c of the manual focus ring 724, which in turn radially fits into an outer diameter portion 712b of the fixed barrel 712. The low-friction sheet 733 serves to reduce friction in a rotating ring mechanism in which the manual focus ring 724 rotates relatively to the fixed barrel 712 around the optical axis.
[0118] The large diameter portion 722a of the roller 722 and the mount side end surface 724b of the manual focus ring are in contact with each other under a pressure applied thereto by the force of the wave washer 726 pressing the ultrasonic motor 725 toward the front of the lens. Similarly, the small diameter portion 722b of the roller 722 and the joining member 729 are in contact with each other under a moderate pressure applied thereto by the force of the wave washer 726 pressing the ultrasonic motor 725 toward the front of the lens. The movement of the wave washer 726 toward the mount direction is restricted by a washer 732 bayonet-coupled to the fixed barrel 712, and the spring force (biasing force) generated by the wave washer 726 is transmitted to the ultrasonic motor 725 and further to the roller 722, and also serves as a pressing force of the manual focus ring 724 against the mount side end surface 712a of the fixed barrel 712. In other words, the manual focus ring 724 is assembled in a state where it is pressed against the mount side end surface 712 a of the fixed barrel 712 via the low friction sheet 733 .
[0119] Therefore, when the ultrasonic motor 725 is driven to rotate relative to the fixed cylinder 712 by a control unit (not shown), the joining member 729 is in frictional contact with the small diameter portion 722b of the roller 722, so that the roller 722 rotates around the center of the shaft 720f. When the roller 722 rotates around the shaft 720f, the rotation transmission ring 720 rotates around the optical axis (autofocus operation).
[0120] Furthermore, when a rotational force about the optical axis is applied to the manual focus ring 724 from a manual operation input unit (not shown), the mount side end face 724b of the manual focus ring 724 is in pressure contact with the large diameter portion 722a of the roller 722, so that the roller 722 rotates about the axis 720f due to frictional force. When the large diameter portion 722a of the roller 722 rotates about the axis 720f, the rotation transmission ring 720 rotates about the optical axis. At this time, the ultrasonic motor 725 does not rotate due to the frictional holding force between the rotor 725c and the stator 725b (manual focus operation).
[0121] Two focus keys 728 are attached to the rotation transmission ring 720 at positions facing each other, and the focus keys 728 fit into notches 715b provided at the tip of the cam ring 715. Therefore, when an autofocus operation or a manual focus operation is performed and the rotation transmission ring 720 is rotated around the optical axis, the rotational force is transmitted to the cam ring 715 via the focus keys 728. When the cam ring is rotated around the optical axis, the rear group barrel 716, whose rotation is restricted by the cam rollers 717a and the linear guide grooves 713a, advances and retreats along the cam grooves 715a of the cam ring 715 by the cam rollers 717b. This drives the focus lens 702 and performs the focus operation.
[0122] Here, we have described an interchangeable lens barrel for a single-lens reflex camera as the optical device of the present invention, but the present invention can be applied to optical devices that have an ultrasonic motor in the drive section, regardless of the type of camera, such as compact cameras, electronic still cameras, and camera-equipped portable information terminals.
[0123] (Vibration device and dust removal device) 2. Description of the Related Art Vibration devices that are used for transporting, removing, and the like of particles, powder, and droplets are widely used in electronic devices and the like.
[0124] A dust removing device using the piezoelectric element of the present invention will be described below as an example of the vibration device of the present invention.
[0125] A dust removing device according to the present invention is characterized in that it comprises a vibrating body having the piezoelectric element or the laminated piezoelectric element disposed on a diaphragm.
[0126] 9(a) and 9(b) are schematic diagrams showing one embodiment of the dust removal device of the present invention. Dust removal device 310 is composed of a plate-shaped piezoelectric element 330 and a vibration plate 320. Piezoelectric element 330 may be the laminated piezoelectric element of the present invention. The material of vibration plate 320 is not limited, but when dust removal device 310 is used in an optical device, a light-transmitting material or a light-reflective material can be used for vibration plate 320.
[0127] FIG. 10 is a schematic diagram showing the configuration of the piezoelectric element 330 in FIG. 9. FIGS. 10(a) and 10(c) show the configuration of the front and back surfaces of the piezoelectric element 330, and FIG. 10(b) shows the configuration of the side surface. As shown in FIG. 9, the piezoelectric element 330 is composed of a piezoelectric material 331, a first electrode 332, and a second electrode 333, and the first electrode 332 and the second electrode 333 are arranged to face the plate surface of the piezoelectric material 331. As in FIG. 9, the piezoelectric element 330 may be a laminated piezoelectric element of the present invention. In that case, the piezoelectric material 331 has an alternating structure of piezoelectric material layers and internal electrodes, and the internal electrodes are alternately short-circuited with the first electrode 332 or the second electrode 333, so that a driving waveform with a different phase can be applied to each layer of the piezoelectric material. In FIG. 10(c), the surface on which the first electrode 332 protruding in front of the piezoelectric element 330 is disposed is referred to as the first electrode surface 336, and in FIG. 10(a), the surface on which the second electrode 333 protruding in front of the piezoelectric element 330 is disposed is referred to as the second electrode surface 337.
[0128] Here, the electrode surface in the present invention refers to the surface of the piezoelectric element on which the electrode is disposed. For example, the first electrode 332 may extend around the second electrode surface 337 as shown in FIG.
[0129] As shown in Figures 9(a) and 9(b), the piezoelectric element 330 and the diaphragm 320 are fixed to the plate surface of the diaphragm 320 by a first electrode surface 336 of the piezoelectric element 330. Then, by driving the piezoelectric element 330, stress is generated between the piezoelectric element 330 and the diaphragm 320, and out-of-plane vibration is generated in the diaphragm. The dust removal device 310 of the present invention is a device that removes foreign matter such as dust attached to the surface of the diaphragm 320 by the out-of-plane vibration of the diaphragm 320. The out-of-plane vibration means an elastic vibration that displaces the diaphragm in the optical axis direction, that is, in the thickness direction of the diaphragm.
[0130] FIG. 11 is a schematic diagram showing the vibration principle of the dust removal device 310 of the present invention. FIG. 11(a) shows a state in which an alternating voltage of the same phase is applied to a pair of left and right piezoelectric elements 330 to generate out-of-plane vibration in the vibration plate 320. The polarization direction of the piezoelectric material constituting the pair of left and right piezoelectric elements 330 is the same as the thickness direction of the piezoelectric elements 330, and the dust removal device 310 is driven in a seventh vibration mode. FIG. 11(b) shows a state in which an alternating voltage of an opposite phase, which is 180° out of phase, is applied to the pair of left and right piezoelectric elements 330 to generate out-of-plane vibration in the vibration plate 320. The dust removal device 310 is driven in a sixth vibration mode. The dust removal device 310 of the present invention is a device that can effectively remove dust attached to the surface of the vibration plate by using at least two vibration modes appropriately.
[0131] (Imaging device) Next, the imaging device of the present invention will be described. The imaging device of the present invention is an imaging device having at least the dust removal device and an imaging element unit, and is characterized in that the vibration plate of the dust removal device is provided on the light receiving surface side of the imaging element unit. Figures 12 and 13 are diagrams showing a digital single-lens reflex camera that is an example of a preferred embodiment of the imaging device of the present invention.
[0132] Fig. 12 is a front perspective view of the camera body 601 as viewed from the subject side, with the photographing lens unit removed. Fig. 13 is an exploded perspective view showing a schematic configuration inside the camera, for explaining the peripheral structure of the dust removal device and the imaging unit 400 of the present invention.
[0133] A mirror box 605 to which a photographing light beam that has passed through a photographing lens is provided within the camera body 601, and a main mirror (quick return mirror) 606 is disposed within the mirror box 605. The main mirror 606 can be held at an angle of 45° with respect to the photographing optical axis in order to guide the photographing light beam in the direction of a pentagonal roof mirror (not shown), or held at a position retracted from the photographing light beam in order to guide it in the direction of an image sensor (not shown).
[0134] A mirror box 605 and a shutter unit 200 are arranged, in that order from the subject side, on the subject side of the main body chassis 300, which forms the framework of the camera body. In addition, an imaging unit 400 is arranged on the photographer side of the main body chassis 300. The imaging unit 400 is installed such that the imaging surface of the imaging element is spaced a predetermined distance from and adjusted to be parallel to the attachment surface of a mount section 602, which serves as a reference for attaching a photographing lens unit.
[0135] Here, a digital single-lens reflex camera has been described as the imaging device of the present invention, but the imaging device may also be a camera with an interchangeable lens unit, such as a mirrorless digital single-lens camera that does not have a mirror box 605. The imaging device may also be applied to video cameras with interchangeable lens units, copiers, facsimiles, scanners, and other imaging devices or electronic and electrical devices equipped with imaging devices, particularly devices that require the removal of dust adhering to the surfaces of optical components.
[0136] (Piezoelectric acoustic components) Next, the piezoelectric acoustic component of the present invention will be described. The piezoelectric acoustic component of the present invention is characterized by being provided with the piezoelectric element or the laminated piezoelectric element. Piezoelectric acoustic components include speakers, buzzers, microphones, and surface acoustic wave (SAW) elements.
[0137] (electronic equipment) Next, an electronic device of the present invention will be described. The electronic device of the present invention is characterized in that it is provided with the piezoelectric acoustic component described above. Fig. 14 is an overall perspective view of a main body 931 of a digital camera, which is an example of a preferred embodiment of the electronic device of the present invention, as viewed from the front.
[0138] An optical device 901, a microphone 914, a strobe light emitting unit 909, and an auxiliary light unit 916 are arranged on the front of the main body 931. The microphone 914 is shown by a dashed line as it is built into the main body. A hole is provided in front of the microphone 914 to pick up sounds from the outside.
[0139] A power button 933, a speaker 912, a zoom lever 932, and a release button 908 for performing a focusing operation are arranged on the top surface of the main body 931. The speaker 912 is incorporated inside the main body 931 and is indicated by a dashed line. A hole is provided in front of the speaker 912 to transmit sound to the outside.
[0140] The piezoelectric acoustic component of the present invention is used in at least one of the microphone 914, the speaker 912, and the surface acoustic wave element.
[0141] Here, a digital camera has been described as an example of the electronic device of the present invention, but the electronic device of the present invention can also be applied to electronic devices having various piezoelectric acoustic components, such as audio playback devices, audio recording devices, mobile phones, and information terminals.
[0142] (Ultrasound probe) Next, the ultrasonic probe of the present invention will be described. The ultrasonic probe of the present invention is characterized in that it has the piezoelectric element and transmits and receives waves by the piezoelectric element.
[0143] FIG. 15 is a schematic cross-sectional view showing one embodiment of the ultrasonic probe of the present invention. The ultrasonic probe 1100 in Fig. 15 is composed of a piezoelectric element 1101, a backing material 1102, an acoustic matching layer 1103, and an acoustic lens 1104. As shown in Fig. 15, a plurality of piezoelectric elements 1101 are arranged and bonded on the backing material 1102, and an acoustic matching layer 1103 for matching acoustic impedance is provided on the opposite surface, which serves as the transmitting and receiving surface.
[0144] Acoustic matching layer 1103 may be a single layer or multiple layers, and preferably is two or more layers. Materials that can be used for acoustic matching layer 1103 include, for example, carbon, aluminum, aluminum alloy (e.g., AL-Mg alloy), magnesium alloy, Macol glass, glass, fused quartz, copper graphite, polyethylene, polypropylene, polycarbonate, ABC resin, polyphenylene ether, ABS resin, AAS resin, AES resin, nylon, polyamideimide, polyethylene terephthalate, polycarbonate, epoxy resin, urethane resin, etc.
[0145] In addition, the backing material 1102 can be made of thermoplastic resins such as natural rubber, ferrite rubber, epoxy resin, vinyl chloride, polyvinyl butyral, ABS resin, polyurethane, polyvinyl alcohol, polyethylene, polypropylene, polyacetal, polyethylene terephthalate, fluororesin, polyethylene glycol, and polyethylene terephthalate, or these mixed with metal powder, or a super-hard material such as tungsten carbide.
[0146] Piezoelectric element 1101 may be one unit or divided into multiple pieces. Fig. 15 shows an example in which it is divided. A flexible cable (not shown) is connected to the electrodes of each piezoelectric element, allowing signals transmitted and received by the piezoelectric element to be input and output. Acoustic lens 1104 is bonded to acoustic matching layer 1103. Acoustic lens 1104 is a member for converging ultrasonic waves transmitted from piezoelectric element 1101 toward the subject, and has an arc shape in the example of Fig. 15. Note that, as a material for acoustic lens 1104, rubber mainly composed of silicone resin (rubber), for example, is generally used.
[0147] When using this ultrasonic probe 1100, an alternating voltage is applied to the piezoelectric element 1101 through a flexible cable, and the piezoelectric element is vibrated by the piezoelectric effect, causing the piezoelectric element 1101 to transmit ultrasonic waves. At this time, if the acoustic impedance of the subject on which the ultrasonic waves are applied is small, or if the ultrasonic waves are applied to the subject through water or air, the presence of the acoustic matching layer 1103 makes it possible to suppress reflected waves caused by large changes in acoustic impedance, and the ultrasonic waves can be efficiently irradiated to the subject. Then, at the time of reception, the piezoelectric element 1101 vibrates due to the ultrasonic waves reflected from inside the subject, and this vibration is electrically converted by the piezoelectric effect to obtain a received signal. At the time of transmission and reception, conversion between electrical energy and mechanical energy is performed, and the conversion efficiency at this time depends on the magnitude of the electromechanical coupling coefficient.
[0148] (Ultrasound diagnostic system) Next, an ultrasonic diagnostic system of the present invention will be described. The ultrasonic diagnostic system of the present invention is characterized by having at least the ultrasonic probe and an image output unit. FIG. 16 is a schematic diagram showing one embodiment of the ultrasonic diagnostic device of the present invention. The ultrasonic diagnostic device 1110 of FIG. 16 is composed of an ultrasonic probe 1100, a cable 1111, a drive control unit 1113, an image output unit 112, and an image processing unit 1114. The flexible cable of the ultrasonic probe 1100 and the drive control unit 1113 are connected by a cable 1111, and an alternating voltage is applied from the drive control unit 1113 to the piezoelectric element 1101 of the ultrasonic probe 1100 via the cable 1111. When ultrasonic waves are irradiated from the ultrasonic probe 1100 into the subject, the ultrasonic waves reflected from inside the subject are converted into electrical signals by the ultrasonic probe again, and input to the image processing unit 1114 through the cable 1111. The image processing unit 1114 creates image data by performing calculations based on delay times and changes in signal strength relative to the alternating voltage output from the drive control unit 1113. The created image data is output to an image output unit 1112 .
[0149] 16, the image processing unit 1114 receives the electric signal of the ultrasonic probe 1100 through the cable 1111, but the signal may be input to the image processing unit 1114 wirelessly. Furthermore, the image processing may be performed remotely via a network line, not at the site where the diagnosis is made using the ultrasonic probe 1100. Similarly, the image output unit 1112 may be remotely located via wireless or remotely located via a network line.
[0150] As described above, the piezoelectric element and laminated piezoelectric element of the present invention can be suitably used in liquid ejection heads, liquid ejection devices, ultrasonic motors, optical instruments, vibration devices, dust removal devices, imaging devices, piezoelectric acoustic components, electronic devices, ultrasonic probes and ultrasonic diagnostic systems.
[0151] By using the piezoelectric element and laminated piezoelectric element of the present invention, it is possible to provide a liquid ejection head having a nozzle density and ejection speed equal to or higher than those achieved by using a piezoelectric element containing lead.
[0152] By using the liquid ejection head of the present invention, it is possible to provide a liquid ejection device having an ejection speed and ejection accuracy equal to or greater than those of a liquid ejection device using a piezoelectric element containing lead.
[0153] By using the piezoelectric element of the present invention, it is possible to provide a vibration actuator having a vibrating body on which the piezoelectric element is arranged and a contact body which comes into contact with the vibrating body.
[0154] By using the piezoelectric element and multilayer piezoelectric element of the present invention, it is possible to provide an ultrasonic motor having driving force and durability equal to or greater than those achieved by using a piezoelectric element containing lead.
[0155] By using the ultrasonic motor of the present invention, it is possible to provide an optical device having durability and operating accuracy equal to or greater than those of a piezoelectric element containing lead.
[0156] By using the piezoelectric element and laminated piezoelectric element of the present invention, it is possible to provide a vibration device having vibration capacity and durability equal to or greater than that of a piezoelectric element containing lead.
[0157] By using the vibration device of the present invention, it is possible to provide a dust removal device that has dust removal efficiency and durability equal to or greater than those of a dust removal device that uses a piezoelectric element containing lead.
[0158] By using the dust removing device of the present invention, it is possible to provide an imaging device having a dust removing function equal to or better than that of a device using a piezoelectric element containing lead.
[0159] By using a piezoelectric acoustic component including the piezoelectric element or multilayer piezoelectric element of the present invention, it is possible to provide electronic equipment that has sound generation properties equal to or better than those achieved by using a piezoelectric element containing lead.
[0160] By using the piezoelectric element of the present invention, it is possible to provide an ultrasonic probe having transmission and reception performance equal to or better than that of a piezoelectric element containing lead. It is also possible to provide an ultrasonic probe equipped with a transducer having a piezoelectric element.
[0161] By using the ultrasonic probe of the present invention, it is possible to provide an ultrasonic diagnostic system having a receiving unit that receives a signal output from the ultrasonic probe and has driving efficiency equal to or greater than that of a piezoelectric element containing lead.
[0162] The piezoelectric material of the present invention can be used in devices such as ultrasonic vibrators, piezoelectric actuators, piezoelectric sensors, and ferroelectric memories, in addition to liquid ejection heads and motors. EXAMPLES
[0163] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0164] The piezoelectric ceramic of the present invention was produced. Example 1 The raw powders used were barium titanate (BaTiO3, Ba / Ti=0.9985) with an average particle size of 100 nm, calcium titanate (CaTiO3, Ca / Ti=0.9978), calcium zirconate (CaZrO3, Ca / Zr=0.999), trimanganese tetroxide (Mn3O4), bismuth oxide (Bi2O3), tungsten oxide (WO3), and barium carbonate to adjust the ratio a of the sum of the moles of Ba and Ca to the sum of the moles of Ti and Zr. These raw powders were mixed together in a composition formula (Ba 0.86 , Ca 0.14 ) 0.9994 (Ti 0.93 ,Zr 0.07 )O3 ratio. The metal oxide was added to 100 parts by mass of the first subcomponent Mn, the second subcomponent Bi, and the third subcomponent W in a ratio shown in Table 1 in terms of metal, that is, the Mn content was 0.160 parts by mass in terms of metal, the Bi content was 0.190 parts by mass in terms of metal, and the W content was 0.312 parts by mass in terms of metal. Mixing was performed by dry mixing for 24 hours using a ball mill. In order to granulate the obtained mixed powder, 3 parts by mass of PVA binder was attached to the mixed powder surface using a spray dryer device.
[0165] Next, the obtained granulated powder was filled into a metal mold, and a molding pressure of 200 MPa was applied using a press molding machine to produce a disk-shaped compact. This compact may be further pressed using a cold isostatic pressing machine.
[0166] The obtained green body was placed in an electric furnace and held at a maximum temperature of 1300 to 1400° C. for 4 hours, and then sintered in an air atmosphere for a total of 24 hours to obtain a sintered body made of the piezoelectric material of the present invention.
[0167] The average equivalent circular diameter and relative density of the crystal grains constituting the obtained sintered body were evaluated. As a result, the average equivalent circular diameter was 8.5 μm, and the relative density was 95% or more. A polarizing microscope was mainly used to observe the crystal grains. A scanning electron microscope (SEM) was used to specify the grain size of small crystal grains. The average equivalent circular diameter was calculated from the observation results. The relative density was evaluated using the theoretical density calculated from the lattice constant obtained from X-ray diffraction and the weighed composition, and the actual density measured by the Archimedes method.
[0168] Next, the composition of the sintered bodies was evaluated by ICP atomic emission spectroscopy. In all piezoelectric materials, the weighed composition of Ba, Ca, Ti, Zr, Mn, Bi and W was consistent with the composition after sintering.
[0169] The sintered body was then polished to a thickness of 0.5 mm and its crystal structure was analyzed by X-ray diffraction, revealing only peaks corresponding to the perovskite structure.
[0170] (d 31 Evaluation element) d 31 As an evaluation element, both sides of the sintered piezoelectric body were polished to a thickness of 0.5 mm, and annealed in an electric furnace at 900°C in air to form gold electrodes with a thickness of 400 nm on both sides of the piezoelectric body by DC sputtering. A 30 nm titanium film was formed between the electrode and the piezoelectric body as an adhesive layer. This piezoelectric body with electrodes was cut using a dicer to produce a rectangular piezoelectric element of 10 mm x 2.5 mm x 0.5 mm. The obtained piezoelectric element was polarized by setting the surface of a hot plate to 60°C to 100°C and applying an electric field of 1 kV / mm between the electrodes of the piezoelectric element on the hot plate for 30 minutes.
[0171] (d 33 Evaluation element) d 33For the evaluation element, both sides of the sintered piezoelectric body were polished, and a plate-shaped piezoelectric body of 5.0 mm x 12.0 mm x 0.90 mm was created by cutting with a dicer. A gold film of 400 nm was then formed by DC sputtering, and the gold formed on the surface was polished and removed to form gold electrodes on the sides of the plate-shaped piezoelectric body. A titanium film of 30 nm was formed as an adhesive layer between the electrode and the piezoelectric body. This plate-shaped piezoelectric body with electrodes was cut again with a dicer to create a rectangular column-shaped piezoelectric element of 0.80 mm x 0.80 mm x 5.0 mm. The obtained piezoelectric element was polarized by applying an electric field of 1 kV / mm between the electrodes of the piezoelectric element for 30 minutes in oil set to 80 to 100 degrees Celsius.
[0172] (Piezoelectric property evaluation) In the following, as static characteristics of the piezoelectric elements having the piezoelectric material of the present invention and the piezoelectric material corresponding to the comparative example, the piezoelectric constant d 31 and the piezoelectric constant d 33 was evaluated using the resonance-antiresonance method. to and T C The capacitance was measured and calculated using an impedance analyzer (Agilent Technologies 4194A) while changing the temperature of the sample. At the same time, the temperature dependence of the dielectric tangent was also measured using the impedance analyzer. The temperature of the sample was first cooled from room temperature to -100°C and then heated to 150°C. to is the temperature at which the crystal system changes from tetragonal to orthorhombic. The dielectric constant was measured while cooling the sample, and the temperature at which the value of the dielectric constant differentiated with respect to the sample temperature was maximized. T C is the temperature at which the dielectric constant becomes maximum near the phase transition temperature between the ferroelectric phase (tetragonal phase) and the paraelectric phase (cubic phase), and is defined as the temperature at which the dielectric constant becomes maximum when the dielectric constant is measured while the sample is heated.
[0173] Examples 2 to 31 and Comparative Examples 1 to 22 were prepared using the same material compositions as in Example 1 and were evaluated in the same manner.
[0174] [Table 1] Table 2 shows the piezoelectric constants d at room temperature for the examples and comparative examples shown in Table 1. 31 and the piezoelectric constant d 33 , electromechanical coupling coefficient k 33 , piezoelectric constant d 33 rate of change of dielectric tangent tanδ, Curie temperature T c , phase transition temperature T to , summarized.
[0175] [Table 2]
[0176] FIG. 18 shows the piezoelectric constant d 33 The temperature dependence of d 33 The rate of change was calculated using formula (3) from the graph in FIG. 18. Comparative Example 1 has the same composition as Example 1 except that it does not contain W. 33 The change rate is 0.332 and the W content is 0.312 in Example 1. 33 The change rate is larger than the change rate of 0.203. In addition, in Comparative Example 2 in which the W content is 0.052, 33 The rate of change is smaller, but d 33 was low at 228 pm / V.
[0177] Figure 17 shows the piezoelectric constant d 33 The changes in the piezoelectric constant d 33 When the content is at a certain level, specifically 0.100 or more, the piezoelectric constant d 33 The piezoelectric constant d 33 The d value was 240 pm / V or more, which is expected to satisfy the performance of the piezoelectric device. 33The piezoelectric constant d of the piezoelectric material of Comparative Example 3 is 258 pm / V, but is 248 pm / V, which is low. Although the material satisfies 240 pm / V, the average grain size is large at 15 μm, and chipping is observed during cutting, making the material poor in processability. Therefore, the piezoelectric material of Comparative Example 3 has a low effective piezoelectric constant d 33 was more than 5% smaller than that obtained from the sample of Comparative Example 3.
[0178] In Comparative Example 4, the Ca content x is small at 0.080. Therefore, Tc is 106°C and T to The temperature was −33° C. Therefore, compared with Example 23 in which the Ca content x was 0.085 and the Ti, Zr, Mn, Bi, and W contents were the same as those in Comparative Example 4, 33 was 42 pm / V higher.
[0179] In Comparative Example 5, the Ca content x is large at 0.315. When the X-ray diffraction was measured, the CaTiO3 phase was detected. 33 The rate of change was 0.271, below 0.3, and was stable with respect to temperature, but the piezoelectric constant d33 at room temperature was 216 pm / V, below 240 pm / V.
[0180] In Comparative Example 8, the Zr content y is large at 0.09. Therefore, the Curie temperature Tc is 84° C., which is lower than 90° C. to The phase transition temperature is now within the practical temperature range, exceeding 0°C at 2°C. 33 The rate of change was large at 0.364, and the dielectric tangent tan δ was also large at 0.16.
[0181] In Comparative Example 11, the Zr content y is small at 0.020. Compared with Example 21 (y=0.070) with the same Ca content, the piezoelectric constant d 33 was 68 pm / V lower.
[0182] In Comparative Example 27, abnormal grain growth was observed because a was small at 0.985. The grain size was large at 50 μm, and the material was poor in processability. The piezoelectric constant d 33 were 211 pm / V and below 240 pm / V.
[0183] In Comparative Example 28, since a was large at 1.004, the growth of the crystal grains was poor and the grain size was small at 1.6 μm. 33 was 216 pm / V, which is less than 240 pm / V, and the dielectric tangent tan δ was large at 0.015.
[0184] In Comparative Example 17, the Bi content is small at 0.04. to At this time, d 33 The rate of change was large at 0.372.
[0185] In Comparative Example 29, the Bi content is large at 0.26. 33 Although the rate of change was small at 0.201, the piezoelectric constant d33 at room temperature was 204 pm / V, which was less than 240 pm / V.
[0186] Example 32 Barium titanate (BaTiO3), calcium titanate (CaTiO3), calcium zirconate (CaZrO3), manganese tetroxide (Mn3O4), tungsten oxide (WO3), bismuth oxide (Bi2O3), and a glass assistant containing Si and B (containing 30 to 50 mass% SiO2 and 21.1 mass% B2O3) were weighed out to obtain the composition of Example 32 in Table 1. The weighed raw material powders were mixed and mixed overnight in a ball mill to obtain a mixed powder.
[0187] PVB was added to the obtained mixed powder and mixed, and then the mixture was formed into a sheet by a doctor blade method to obtain a green sheet having a thickness of 50 μm.
[0188] A conductive paste for the internal electrodes was printed on the green sheets. A 60% Ag-40% Pd alloy paste was used as the conductive paste. Nine green sheets coated with the conductive paste were stacked, and the stack was fired at 1200°C for 5 hours to obtain a sintered body. The sintered body was cut into pieces measuring 10 mm x 2.5 mm, and the sides were polished. A pair of external electrodes (first and second electrodes) that alternately short-circuit the internal electrodes were formed by Au sputtering, to produce a multilayer piezoelectric element as shown in Figure 2(b).
[0189] When the internal electrodes of the obtained multilayer piezoelectric element were observed, it was found that the electrode material, Ag-Pd, was formed alternately with the piezoelectric material.
[0190] Prior to the evaluation of the piezoelectricity, the sample was subjected to a polarization treatment by heating the sample to 100°C in an oil bath, applying a voltage of 1 kV / mm between the first and second electrodes for 30 minutes, and then cooling the sample to room temperature with the voltage still applied.
[0191] When the piezoelectric properties of the obtained multilayer piezoelectric element were evaluated, it was found to have sufficient insulation properties and to have excellent piezoelectric properties equivalent to those of the piezoelectric material of Example 1.
[0192] (Example 33) A mixed powder was prepared in the same manner as in Example 32. The obtained mixed powder was calcined in the air at 1000°C for 3 hours while rotating in a rotary kiln to obtain a calcined powder. The calcined powder obtained was crushed using a ball mill. PVB was added to the crushed powder obtained and mixed, and then a sheet was formed by a doctor blade method to obtain a green sheet with a thickness of 50 μm. A conductive paste for an internal electrode was printed on the green sheet. Ni paste was used as the conductive paste. Nine green sheets coated with the conductive paste were stacked, and the stack was thermocompressed.
[0193] The thermocompression-bonded laminate was sintered in a tubular furnace. Firing was performed in air up to 300°C, and after removing the binder, the atmosphere was changed to a reducing atmosphere (H2:N2 = 2:98, oxygen concentration 2 × 10 -6 The oxygen concentration was changed to 30 Pa from below 1000°C and the sample was cooled to room temperature.
[0194] The sintered body thus obtained was cut into pieces measuring 10 mm × 2.5 mm, and the sides of the pieces were then polished. A pair of external electrodes (first and second electrodes) that alternately short-circuited the internal electrodes were then formed by Au sputtering, resulting in a multilayer piezoelectric element as shown in Figure 2(b).
[0195] Observation of the internal electrodes of the obtained multilayer piezoelectric element revealed that Ni, the electrode material, was alternately formed with the piezoelectric material layers. The obtained multilayer piezoelectric element was subjected to a polarization treatment by applying an electric field of 1 kV / mm for 30 minutes in an oil bath maintained at 100°C. Evaluation of the piezoelectric properties of the obtained multilayer piezoelectric element revealed that it had sufficient insulation and was capable of obtaining good piezoelectric properties equivalent to those of the piezoelectric element of Example 32.
[0196] (Example 34) A liquid ejection head as shown in Fig. 3 was produced using the piezoelectric element of Example 1. The ejection of ink in accordance with the input electrical signal was confirmed.
[0197] (Example 35) 4 was produced using the liquid ejection head of Example 34. The ejection of ink in accordance with the input electrical signal was observed on a recording medium.
[0198] (Example 36) An ultrasonic motor as shown in Fig. 6(a) was produced using the piezoelectric element of Example 1. Rotation of the motor in response to application of an alternating voltage was confirmed.
[0199] (Example 37) An optical device shown in Fig. 7 was manufactured using the ultrasonic motor of Example 36. Autofocus operation in response to application of an alternating voltage was confirmed.
[0200] (Example 38) A dust removal device shown in Fig. 9 was produced using the piezoelectric element of Example 1. When plastic beads were scattered and an alternating voltage was applied, a good dust removal rate was confirmed.
[0201] (Example 39) 12 was produced using the dust removing device of Example 38. When it was operated, dust on the surface of the imaging unit was removed satisfactorily, and an image without dust defects was obtained.
[0202] (Example 40) An electronic device shown in Fig. 14 was fabricated using the piezoelectric element of Example 1. In the fabricated electronic device, speaker operation in response to application of an alternating voltage was confirmed.
[0203] (Example 41) An ultrasonic probe shown in Fig. 15 was fabricated using the piezoelectric element of Example 1. In the fabricated ultrasonic probe, ultrasonic waves were transmitted by application of an alternating voltage, and a received signal due to reflection from inside the subject was confirmed.
[0204] (Example 42) An ultrasonic diagnostic system shown in Fig. 16 was fabricated using the ultrasonic probe of Example 41. When the fabricated ultrasonic diagnostic system was operated, a clear image of the inside of the subject was output.
[0205] (Example 43) A liquid ejection head as shown in Fig. 3 was produced using the laminated piezoelectric element of Example 32. The ejection of ink in response to an input electrical signal was confirmed.
[0206] (Example 44) 4 was produced using the liquid ejection head of Example 43. The ejection of ink in accordance with the input electrical signal was observed on a recording medium.
[0207] (Example 45) An ultrasonic motor as shown in Fig. 6(b) was fabricated using the laminated piezoelectric element of Example 32. Rotation of the motor in response to application of an alternating voltage was confirmed.
[0208] (Example 46) An optical device shown in Fig. 7 was manufactured using the ultrasonic motor of Example 45. Autofocus operation in response to application of an alternating voltage was confirmed.
[0209] (Example 47) A dust removal device as shown in Fig. 9 was produced using the multilayer piezoelectric element of Example 32. When plastic beads were scattered and an alternating voltage was applied, a good dust removal rate was confirmed.
[0210] (Example 48) 12 was produced using the dust removing device of Example 47. When it was operated, dust on the surface of the imaging unit was removed satisfactorily, and an image without dust defects was obtained.
[0211] (Example 49) The laminated piezoelectric element of Example 32 was used to fabricate the electronic device shown in Fig. 14. Speaker operation in response to application of an alternating voltage was confirmed. [Industrial Applicability]
[0212] The piezoelectric material of the present invention exhibits good piezoelectricity over a wide range of environmental temperatures. In addition, since it does not contain lead, it places little burden on the environment. Therefore, the piezoelectric material of the present invention can be used without problems in devices that use a large amount of piezoelectric material, such as liquid ejection heads, ultrasonic motors, dust removal devices, and ultrasonic diagnostic systems. [Explanation of symbols]
[0213] 1. First electrode 2 Piezoelectric Materials Department 3 Second electrode 51 First electrode 53 Second Electrode 54 Piezoelectric material layer 55 Internal electrode 501 First electrode 503 Second Electrode 504 Piezoelectric material layer 505a internal electrode 505b Internal electrode 506a external electrode 506b External electrode 101 Piezoelectric element 102 Individual liquid chamber 103 Diaphragm 104 Liquid chamber bulkhead 105 Discharge port 106 Communication hole 107 Common liquid chamber 108 Buffer Layer 1011 First electrode 1012 Piezoelectric materials 1013 Second electrode 881 Liquid discharge device 882 Exterior 883 Exterior 884 Exterior 885 Exterior 887 Exterior 890 Recovery Department 891 Recording Department 892 Carriage 896 Device body 897 Automatic feeding section 898 Outlet 899 Conveyor 201 Transducer 202 Rotor 203 Output shaft 204 Transducer 205 Rotor 206 Spring 2011 Elastic Ring 2012 Piezoelectric element 2013 Organic adhesives 2041 Metal Elastic Body 2042 Multilayer Piezoelectric Element 701 Front lens 702 Rear lens (focus lens) 711 Detachable Mount 712 Fixed tube 713 Straight guide tube 714 Front group tube 715 Cam Ring 716 Rear group tube 717 Cam Roller 718 Axle screw 719 Lola 720 Rotation Transmission Ring 722 Coro 724 Manual Focus Ring 725 Ultrasonic Motor 726 Wave washer 727 Ball Race 728 Focus Key 729 Joint materials 732 Washer 733 Low Friction Sheet 310 Dust removal equipment 320 diaphragm 330 Piezoelectric element 331 Piezoelectric Materials 332 First electrode 333 Second Electrode 336 First electrode surface 337 Second electrode surface 601 Camera body 602 Mounting section 605 Mirror Box 606 Main Mirror 200 Shutter unit 300 Main Chassis 400 Imaging unit 901 Optical equipment 908 Release button 909 Strobe light emitter 912 Speaker 914 Mike 916 Auxiliary Light Unit 931 Main unit 932 Zoom Lever 933 Power button 1100 Ultrasound Probe 1101 Piezoelectric element 1102 Backing layer 1103 Acoustic matching layer 1104 Acoustic Lens 1110 Ultrasound diagnostic equipment 1111 Cable 1112 Image output unit 1113 Drive control unit 1114 Image processing section
Claims
1. A piezoelectric material containing an oxide having a perovskite structure containing Ba, Ca, Ti, and Zr, Mn, Bi, and W, x, which is a molar ratio of Ca to the sum of Ba and Ca, 0.085≦x≦0.140, y, which is a molar ratio of Zr to the sum of Ti and Zr, 0.025≦y≦0.085, the sum of the Ba and the Ca relative to the sum of the Ti and the Zr is 0.992 or more and 0.9994 or less; In terms of metal, per 100 parts by mass of the oxide, The Mn content is 0.100 parts by mass or more and 0.240 parts by mass or less, The Bi content is 0.050 parts by mass or more and 0.240 parts by mass or less, The content of W is 0.104 parts by mass or more and 0.380 parts by mass or less, A piezoelectric material, characterized in that the average equivalent circular diameter of the crystals of the piezoelectric material is 5.3 μm or more and 9.7 μm or less.
2. The piezoelectric material of claim 1 , wherein the piezoelectric material is poled.
3. The oxide has the following general formula (1): (Ba) 1-x Ca x )a(Ti 1-y Zr y )O 3 (1) 3. The piezoelectric material according to claim 1, wherein the piezoelectric material is represented by (0.085≦x≦0.140, 0.025≦y≦0.085, 0.992≦a≦0.9994).
4. 4. The piezoelectric material according to claim 1, wherein the dielectric tangent of the piezoelectric material at a frequency of 1 kHz is 0.002 or more and 0.009 or less.
5. A piezoelectric body comprising the piezoelectric material according to any one of claims 1 to 4.
6. A piezoelectric element having at least an electrode and a piezoelectric material portion, the piezoelectric material portion including the piezoelectric material according to any one of claims 1 to 4.
7. The piezoelectric element according to claim 6 , wherein the electrodes and the piezoelectric material portions are laminated alternately.
8. 8. The piezoelectric element according to claim 7, wherein the electrodes contain Ag and Pd, and a mass ratio M1 / M2 of a mass M1 of the Ag content to a mass M2 of the Pd content satisfies 0.25≦M1 / M2≦4.
0.
9. The piezoelectric element according to claim 7 , wherein the electrodes contain at least one of Ni and Cu.
10. 10. A liquid ejection head comprising: a liquid chamber provided with a vibration portion having the piezoelectric element according to claim 6; and an ejection port communicating with the liquid chamber.
11. A liquid ejection device comprising a mounting portion for an object and the liquid ejection head according to claim 10.
12. 10. A vibration actuator comprising: a vibrating body on which the piezoelectric element according to claim 6 is disposed; and a contact body that comes into contact with the vibrating body.
13. An optical device comprising the vibration actuator according to claim 12 in a drive section.
14. A vibration device having a vibrating body in which the piezoelectric element according to any one of claims 6 to 9 is disposed on a vibration plate.
15. A dust removing device comprising a vibration section including the vibration device according to claim 14.
16. 16. An imaging apparatus comprising at least the dust removal device according to claim 15 and an imaging element unit, wherein a diaphragm of the dust removal device is provided on a light receiving surface side of the imaging element unit.
17. A piezoelectric acoustic component comprising the piezoelectric element according to any one of claims 6 to 9.
18. An ultrasonic probe comprising a transducer having the piezoelectric element according to any one of claims 6 to 9.
19. 20. An ultrasonic diagnostic system comprising: the ultrasonic probe according to claim 18; and a receiving unit that receives a signal output from the ultrasonic probe.
20. An electronic device comprising a piezoelectric element according to any one of claims 6 to 9.
Citation Information
Patent Citations
Production of powdery raw material of easily sintering perovskite solid solution
JP1986053114A
Display instrument
JP1991004121A
Barium titanate and its manufacturing method as well as capacitor
JP2006096652A
Dielectric porcelain composition and electronic component
JP2007269542A
Piezoelectric element, and liquid jet head and ultrasonic motor using the piezoelectric element
JP2008098627A